2022
DOI: 10.1002/jev2.12172
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with mammalian enteric viruses alters outer membrane vesicle production and content by commensal bacteria

Abstract: Intestinal commensal bacteria contribute to maintaining gut homeostasis. Disruptions to the commensal flora are linked to the development and persistence of disease. The importance of these organisms is further demonstrated by the widespread ability of enteric viruses to exploit commensal bacteria to enhance viral infection. These viruses interact directly with commensal bacteria, and while the impact of this interaction on viral infection is well described for several viruses, the impact on the commensal bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 86 publications
(122 reference statements)
4
41
0
Order By: Relevance
“…We also examined changes in the expression of these bacterial genes during HNoV binding. Unlike MNV, HNoV did not significantly alter the expression of the targeted genes, however, the trends in gene expression were, in some cases, similar to MNV and were also consistent with previous RNA-seq analysis [ 12 ]. The observed differential impacts on gene expression between these viruses may be connected to the differing methods by which each type of norovirus attaches to the bacteria.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We also examined changes in the expression of these bacterial genes during HNoV binding. Unlike MNV, HNoV did not significantly alter the expression of the targeted genes, however, the trends in gene expression were, in some cases, similar to MNV and were also consistent with previous RNA-seq analysis [ 12 ]. The observed differential impacts on gene expression between these viruses may be connected to the differing methods by which each type of norovirus attaches to the bacteria.…”
Section: Discussionsupporting
confidence: 88%
“…To further explore this hypothesis that glucose is reducing the expression of key bacterial surface structures, we measured the expression of genes associated with bacterial surface structures previously associated with norovirus interactions (e.g., the flagellum and the outer membrane) [ 1 , 20 ]. We have previously found that norovirus interactions with E. cloacae significantly alters the expression of genes associated with the bacterial outer and trans membranes [ 12 ]. We also know that MNV binding to bacteria is variable, with 10% to 20% of bacteria remaining unbound by MNV following incubation with the virus, which may impact the consistency of gene expression data found in each replicate [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is accompanied by marked changes in the intestinal microbiota due to the infection. Noroviruses are reported in animal studies and in vitro studies on the interaction between the virus and the microbiota during infection [ 20 ]. In vitro experiments have shown that human noroviruses can infect B cells in the presence of bacteria coated with histo-blood group antigens.…”
Section: Acute Gastroenteritismentioning
confidence: 99%